Pengaruh Penerapan Model Problem Based Learning Terhadap Kemampuan Penalaran Matematis Peserta Didik Kelas VIII SMP Negeri 1 Danau Kembar - VIOLA AMELIA PUTRI (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical reasoning ability is very important for students to be able to solve various problems inside and outside the mathematical context. However, in class VIII SMPN 1 Danau Kembar students' mathematical reasoning ability is still low. One effort that can be done to improve students' mathematical reasoning ability is to apply the Problem Based Learning (PBL) model. The purpose of the study was to describe the effect of the Problem Based Learning model on students mathematical reasoning abilities better than students mathematical reasoning by using conventional learning in class VIII SMPN 1 Danau Kembar. The type of research is quasy-experiment and descriptive with a Randomized Control Group Only Design. The research instrument is a test of mathematical reasoning abilities. From the data analysis it was concluded that students' mathematical reasoning abilities that applied the PBL model were better than the students' mathematical reasoning abilities who applied conventional learning, and there was an increase in students' mathematical reasoning abilities while learning to apply the PBL model. Keywords - The Ability Of Mathematical Reasoning, Problem Based Learning Model, Learning Conventional